Proton pump inhibitor use is associated with elevated faecal calprotectin levels. A cross-sectional study on subjects referred for colonoscopy - Lundgren, David; Eklöf, Vincy; Palmqvist, Richard; Hultdin, Johan; Karling, Pontus (Scandinavian journal of gastroenterology, 2019)
Objectives: Faecal Calprotectin (FC) is a sensitive marker for gut inflammation. However, slightly elevated FC levels are also common in subjects without inflammation. We investigated the association between FC and clinical factors including concomitant use of medical therapy in patients with a normal colonoscopy. Material and methods: Out-patients (n = 1263) referred for colonoscopy, performed FC test (CALPRO) the day before the start of bowel preparation. All subjects answered questionnaires that included questions on the present and past health history, concomitant medical treatment and gastrointestinal symptoms (GSRS). A medical record chart review was performed to check for concomitant disease, cause of referral and the result of the colonoscopy including biopsies. Inclusion criteria were a normal colonoscopy. Exclusion criteria were inflammatory bowel disease, colon cancer and high-grade dysplasia. Results: Five hundred ninety subjects fulfilled the inclusion criteria and completed the study. Thirty-six per cent of the subjects had a FC >50 µg/g. In a logistic regression analysis, age (adjusted OR: 1.051; CI: 1.032-1.071), and the use of proton pump inhibitors (adjusted OR: 3.843; CI: 2.338-6.316), non-steroid anti-inflammatory drugs (adjusted OR: 2.411; CI: 1.162-5.002) and acetylsalicylic acid (adjusted OR: 2.934; CI: 1.085-3.448) were significantly associated with an elevated FC (>50 µg/g). Conclusions: More than one-third of the patients with a normal colonoscopy performed in clinical routine had a slightly elevated FC level. Our results emphasise the need for attention to age, the use of proton pump inhibitors, non-steroid anti-inflammatory drugs and acetylsalicylic acid in the interpretation of FC tests in clinical practice.